The impact of violence reduction initiatives on emergency department attendance. Issue 2 (May 2015) - Rainey, SR; Simpson, J; Page, S; Crowley, M; Evans, J; Sheridan, M; Ireland, AJ
Background: Recent violence reduction initiatives in Glasgow have led to a reduction in recorded levels of violent crime. 1 This study evaluates the impact of these initiatives on assault-related emergency department attendances and admissions. Methods: A retrospective observational study conducted in Glasgow Royal Infirmary's emergency department comparing assault-related emergency department attendances and hospital admissions over two 30-day study periods (April 2010 and April 2012). The primary outcome measure was the change in assault-related emergency department attendances. The secondary outcome measure was the impact on assault-related hospital and critical care admissions. Results: In April 2010, there were 6098 emergency department attendances, 301 (4.9%) were due to assault. In April 2012, there were 7236 emergency department attendances, 263 (3.6%) were due to assault, representing a significant reduction in assault-related attendances ( p  < 0.01). There were significant reductions in level 1 admissions 2010  n  = 56 (19.2%), 2012  n  = 36 (14.0%) p  = 0.04 and critical care admissions, 2010  n  = 5 (1.7%), 2012  n  = 1 (0.4%) p  = 0.04. Conclusions: Violence reduction initiatives in Glasgow have contributed to a reduction in assault-related emergency department attendance at Glasgow Royal Infirmary. The reduction in hospital admissions, in particular critical care admissions, suggests a reduction in morbidity and cost to the National Health Service.